Good Countries or Good Projects? : Comparing Macro and Micro Correlates of World Bank and Asian Development Bank Project Performance - Bulman, David (World Bank, Washington, DC, 2015)
This paper examines the micro and macro correlates of aid project outcomes in a sample of 3,821 World Bank projects and 1,342 Asian Development Bank projects. Project outcomes vary much more within countries than between countries: country-level characteristics explain only 10–25 percent of project outcomes. Among macro variables, country growth and the policy environment are significantly positively correlated with project outcomes. Among micro variables, shorter project duration and the presence of additional financing are significantly correlated with better project outcomes. In addition, the track record of the project manager in delivering successful projects is highly significantly correlated with project outcomes. There are few significant differences between the two institutions in the relationship between these variables and project outcomes.